Antimicrobial Efficacy of Mineral Trioxide Aggregate against Therapy Resistant Endodontic Microorganisms - Banu, Mst Laila Akter; Bashar, AKM; Howlader, Md Mujibur Rahman; Alam, Md Shamsul; Hussain, Md Ashraf (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Microorganisms, usually from the dental caries, are the main sources of diseases in dental pulp (root canals) and periapical region. Facultative bacteria and fungi have been identified in therapy resistant persistent endodontic infection. The objectives of this study was to evaluate the antimicrobial efficacy of Mineral Tri Oxide Aggregate (MTA) against therapy resistant endodontic microorganisms. The efficacy of MTA was also compared with that of calcium hydroxide. Six standard bacterial stains were used: Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, bacillus subtilis, Candida albicans and Enterococcus faecalis. The agar diffusion method on Muller- Hilton media was employed. The plates containing media were inoculated with the specified bacterial suspensions. Two standard holes were prepared on each microorganism inoculated plate with a copper puncher and one hole was completely filled with MTA & the other with Ca (OH)2 . The plates were then kept at environmental temperature for one hour to ensure prediffusion and then incubated at 370C for 24 hours. After 24 hours, the diameters of inhibition zones were measured. Tests were replicated for thirty times for each sample and mean values were taken. Zone of inhibition as measured for MTA and Ca (OH)2 were statistically analyzed with Students t-Test and Post Hoc Games Howell Test and were presented as mean ± SD to compare of efficacy of MTA and calcium hydroxide on different microorganisms. Both MTA and Ca(OH)2 were found to produce zone of inhibition against Staphylococcus aureus (ATCC 25923), Pseudomonas aeruginosa (ATCC 27853), , Bacillus subtilis (BTCC 17 ), and Candida albicans (BTCC 493). MTA showed highest activity against S. aureus and lowest activity against P. aeruginosa which was similar to the activity range of Ca (OH)2 against the mentioned organisms. But both of them failed to produce any activity against E. coli and. E. faecalis. MTA was found to produce a lower efficacy than Ca (OH)2 while comparing the zone of inhibition between them and statistically it was significant. Mineral Tri Oxide Aggregate (MTA) showed antimicrobial efficacy against some therapy resistant microorganisms but it did not show antimicrobial efficacy against Escherichia coli and Enterococcus faecalis. MTA was found to produce a lower antimicrobial efficacy than Ca (OH)2. J Bangladesh Coll Phys Surg 2015; 33(3): 140-145